Cyclohepta[c]furan-based fluorophores: Synthesis, optical properties, solvatochromism and DFT study. (August 2017) - Yanagisawa, Tatsuya; Kobayashi, Naoki; Miyatake, Ryuta; Oda, Mitsunori
Abstract: Novel 6 H -cyclohepta[ c ]furan derivatives possessing aryl groups on 1, 3-position were synthesized, and their photophysical behavior were investigated. 1, 3-Diphenyl-5, 7-difomyl derivative showed solvatochromism. As the electron donating ability at 1, 3-positions and the electron withdrawing ability at 5, 7-positions increased, the absorption and emission wavelengths were bathochromically shifted. Theoretical calculations revealed that their photophysical behaviors are reproduced. Highlights: 6 H -Cyclohepta[ c ]furan derivatives possessing aryl groups on 1, 3-position as novel fluorophores were synthesized. Their absorption and emission wavelengths were red-shifted by the substituents at 1, 3-positions and 5, 7-positions. Theoretical calculations revealed that their photophysical behaviors are reproduced.